2023
DOI: 10.3390/molecules28020908
|View full text |Cite
|
Sign up to set email alerts
|

Review on Extraction, Modification, and Synthesis of Natural Peptides and Their Beneficial Effects on Skin

Abstract: Peptides, functional nutrients with a size between those of large proteins and small amino acids, are easily absorbed by the human body. Therefore, they are seeing increasing use in clinical medicine and have revealed immunomodulatory and anti-inflammatory properties which could make them effective in healing skin wounds. This review sorted and summarized the relevant literature about peptides during the past decade. Recent works on the extraction, modification and synthesis of peptides were reviewed. Importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 113 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…The ability of APs to neutralize some endotoxins (in in vivo models) is another of their assets [ 156 ], to which is added their property to prevent the formation of bacterial biofilms [ 157 ]. Furthermore, recent studies have shown that they can potentiate the effects of other antibiotics, and it is feasible to develop medical products with APs for topical application, also considering the antioxidant potential of some of them [ 158 , 159 ]. Currently, attempts are being made to overcome some obstacles, such as bacterial strategies for resistance [ 160 ] and their toxicity through various strategies such as their chemical modification (especially of terminal groups), the use of nanotechnologies and bioinformatics studies [ 157 ], and some APs are already in clinical trials [ 157 ].…”
Section: Drugs As Antibiotic Alternatives or Complementsmentioning
confidence: 99%
“…The ability of APs to neutralize some endotoxins (in in vivo models) is another of their assets [ 156 ], to which is added their property to prevent the formation of bacterial biofilms [ 157 ]. Furthermore, recent studies have shown that they can potentiate the effects of other antibiotics, and it is feasible to develop medical products with APs for topical application, also considering the antioxidant potential of some of them [ 158 , 159 ]. Currently, attempts are being made to overcome some obstacles, such as bacterial strategies for resistance [ 160 ] and their toxicity through various strategies such as their chemical modification (especially of terminal groups), the use of nanotechnologies and bioinformatics studies [ 157 ], and some APs are already in clinical trials [ 157 ].…”
Section: Drugs As Antibiotic Alternatives or Complementsmentioning
confidence: 99%
“…Flavonoids, phenols, amino acids, VC, and other Chinese olive active ingredients can be orally absorbed when ingested but can also be absorbed through the skin, having a high utilization value in the beauty and skincare industry and products ( Nagula and Wairkar, 2019 ; Farjadmand et al, 2021 ; An et al, 2023 ). As a raw material for cosmetic products, Chinese olive can reduce skin irritation and improve and solve skin problems between deep skin care and non-etiological skin problems.…”
Section: Practical Applicationsmentioning
confidence: 99%